Report Of The Asian Multicity Epidemiology Work Group 2002. - Navaratnam, Profesor Madya (Dr.) V. (Pusat Penyelidikan Dadah Dan Ubat-Ubatan Universiti Sains Malaysia, 2002)

(untitled)
The Asian Multicity Epidemiology Work Group AMCEWG)'programme has entered its tenth year in 2002. The Group now consists of twenty-two member cities from South, East, and Central Asia, whereby each member city has established her own drug abuse surveillance system.